Impact of an alpha helix and a cysteine–cysteine disulfide bond on the resistance of bacterial adhesion pili to stress - Baker, Joseph L. (Proc Natl Acad Sci U S A, 2021)
Escherichia coli express adhesion pili that mediate attachment to host cell surfaces and are exposed to body fluids in the urinary and gastrointestinal tracts. Pilin subunits are organized into helical polymers, with a tip adhesin for specific host binding. Pili can elastically unwind when exposed to fluid flow forces, reducing the adhesin load, thereby facilitating sustained attachment. Here we investigate biophysical and structural differences of pili commonly expressed on bacteria that inhabit the urinary and intestinal tracts. Optical tweezers measurements reveal that class 1a pili of uropathogenic E. coli (UPEC), as well as class 1b of enterotoxigenic E. coli (ETEC), undergo an additional conformational change beyond pilus unwinding, providing significantly more elasticity to their structure than ETEC class 5 pili. Examining structural and steered molecular dynamics simulation data, we find that this difference in class 1 pili subunit behavior originates from an [Formula: see text]-helical motif that can unfold when exposed to force. A disulfide bond cross-linking [Formula: see text]-strands in class 1 pili stabilizes subunits, allowing them to tolerate higher forces than class 5 pili that lack this covalent bond. We suggest that these extra contributions to pilus resiliency are relevant for the UPEC niche, since resident bacteria are exposed to stronger, more transient drag forces compared to those experienced by ETEC bacteria in the mucosa of the intestinal tract. Interestingly, class 1b ETEC pili include the same structural features seen in UPEC pili, while requiring lower unwinding forces that are more similar to those of class 5 ETEC pili.